Breeding value and homeostaticity of the spike performance and its constituents in medium tall winter bread wheat (Triticum aestivum L.) accessions in relation to resistance to the pathogens of powdery mildew (Blumeria graminis (DC.)... - A. Yarosh; V. Riabchun; O. Solonechna (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2023)
Identification of sources of group resistance in winter bread to the pathogens B. graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal and S. tritici Rob. et Desm. and of high performance of the spike and its constituents is a necessary and relevant step towards the creation of comprehensively valuable and adaptable genotypes. The paper presents the results of evaluation of the breeding value and homeostaticity of the spike performance and its constituents in medium tall winter bread wheat in relation to resistance to powdery mildew and Septoria leaf blotch. New sources of consistently high group resistance to the powdery mildew and Septoria leaf blotch pathogens have been identified: Kyivska 17, Zorianka, Sicheslava, and Svitiaz (UKR). We have selected accessions with high performance of the spike and its constituents in combination with high breeding value and homeostaticity of these characteristics: the kernel weight per spike (Kyivska 17 (Sc = 1.8; Hom = 21.9) (UKR)); the kernel number per spike (Svitohliad (Sc = 37.8; Hom = 554.1), Stritenska (Sc = 36.4; Hom = 452.5), Svitiaz (Sc = 35.8; Hom = 451.8), MIP Lada (Sc = 33.6; Hom = 572.7) (UKR), and Manella (Sc = 33.1; Hom = 460.8) (NLD)); and the thousand kernel weight (Kyivska 17 (Sc = 42.9; Hom = 1053.7), Sicheslava (Sc = 42.6; Hom = 873.2) (UKR), and Turanus (Sc = 41.3; Hom = 707.5) (AUT)). It was found that the percentage of accessions with high homeostaticity of the thousand kernel weight, the kernel number per spike and the kernel weight per spike was 63.6%, 31.8%, and 22.7%, respectively. In the medium tall winter bread wheat accessions, there were strong positive correlations between the breeding value of the kernel weight per spike and resistance to Septoria leaf blotch (r = 0.77, P < 0.01) and between the kernel number per spike and resistance to powdery mildew (r = 0.71, P < 0.01). Significant positive correlations were observed between the breeding value of the thousand kernel weight and resistance to Septoria leaf blotch (r = 0.61, P < 0.01), between the homeostaticity of the thousand kernel weight and resistance to Septoria leaf blotch (r = 0.51, P < 0.01) and between the breeding value of the kernel number per spike and resistance to Septoria leaf blotch (r = 0.56, P < 0.01). The selected sources of high group resistance to powdery mildew and Septoria leaf blotch, high performance of the spike and its constituents in combination with the breeding value and homeostaticity of these traits are valuable starting materials to create highly promising winter bread wheat cultivars, which would be adaptable to limiting biotic factors.